Capability analysis and simulation for robot-based warehouse automation - Yang, Yubo (Nanyang Technological University, 2023)
Multi-robot system has been widely used in warehouse logistics, but the evaluation and optimization of system performance is still in the trial stage. In this study, we try to quantify the performance of the system as much as possible and give the mathematical model of its quantization parameters. Parameters including but not limited to load, power, congestion, etc., are quantified separately, and the interaction between various performance parameters is also discussed and described by mathematical formulas. At this point, we carried out a quantitative evaluation of the system performance, and we also carried out a simulation at the end to analyze and verify the impact of changes in warehouse layout and system parameters on the system performance. In addition to the analysis and evaluation of the existing system, we also try to propose a property-driven multi-agent design method, which is combined with performance analysis method in order to evaluate the system during the design process. The design method is based on the required properties of system, and the system is designed from the top level to the bottom level. The evaluation method named off-policy is integrated into the model check step of the system design step. The system is evaluated and verified during the design process: if the system is verified to meet the attribute requirements, the design will proceed to the next implementation step; or else, the iterative optimization will be carried out.